Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.36834/cmej.72160
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 on Canadian surgical residents’ education and wellness

Abstract: Background: The COVID-19 pandemic has challenged health care systems. We sought to comprehend the impact of the COVID-19 pandemic on surgical residents’ education and mental well-being across Canada. Methods: An online 51-question survey was distributed to surgical residents across all 17 Canadian post- graduate surgical residency programs. The questionnaire contained questions concerning demographic factors, perceived effects of COVID-19 pandemic on surgical training and residents’ mental health (categoricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, psychological disorders affect even more residents’ quality of life. For example, Alam et al (2022) [ 10 ] reported that during the COVID-19 pandemic, 41% of surgical residents experienced more anxiety than before the pandemic, while in a paper conducted by Mordant et al (2013) [ 11 ], 60% of the trainees had a low level of fatigue, with a little below half of them (44%) reporting having sleep disorder based on the Epworth Sleepiness Score, which is mainly due to in-hospital work time and insufficient educational programs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, psychological disorders affect even more residents’ quality of life. For example, Alam et al (2022) [ 10 ] reported that during the COVID-19 pandemic, 41% of surgical residents experienced more anxiety than before the pandemic, while in a paper conducted by Mordant et al (2013) [ 11 ], 60% of the trainees had a low level of fatigue, with a little below half of them (44%) reporting having sleep disorder based on the Epworth Sleepiness Score, which is mainly due to in-hospital work time and insufficient educational programs.…”
Section: Discussionmentioning
confidence: 99%